Nerovný vývoj světa a rozvojová teorie - Navrátilová, Alice (Masaryk University Press, 2020)
Title in English: Uneven development of the world and development theory. The book explores contemporary theories of development and their historical trajectories. It provides an overview of the main development paradigms according to the Neederven Pieterse´s classification: modernization school, dependency school, human development, neoliberalism, alternative development and postdevelopment. All perspectives are narrated from critical post-structuralist perspective exploring the knowledge-power nexus and each paradigm is linked to actors and institutions that apply particular approach. Special attention is paid to the globalisation processes that have dramatically reshaped historical and contemporary patterns of uneven development. The textbook is tailored to introductory courses of human geography, development studies, social and political sciences as well as to answer to the interest of the general public.